PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT ELANG MAHKOTA TEKNOLOGI TBK PERIODE 2013-2023 - Haristiyadi; Arif Surahman (Journal of Research and Publication Innovation, 2025)
The puRp.ose of this research is to determine the influence of the Current Ratio and Debt to Equity Ratio on the Return on Equity of PT. Elang Mahkota Teknologi, Tbk. during the period 2013-2023. A quantitative method is used to analyze and determine the variables of Current Ratio and Debt to Equity Ratio on Return on Equity both partially and simultaneously, and to identify which variable has the most dominant influence the Return on Equity of PT. Elang Mahkota Teknologi Tbk. Data analysis uses descriptive analysis, classical assumption test, regression analysis, coefficient of determination analysis, and hypothesis testing. Based on the data analysis results, it can be concluded that the Current Ratio does not have a partial effect on the Current Ratio. The results of the test show that the calculated t-value of -0.477 is greater than the t-table value of 2.262 and has a significance level of 0.643 > 0.05. The Debt to Equity Ratio also does not have a partial effect on the Return on Equity. The results of the test show that the calculated t-value of 0.696 is greater than the t-table value of 2.262 and has a significance level of 0.501 > 0.05. Simultaneously, it shows that there is an influence between the Current Ratio and Debt to Equity Ratio on the Return on Equity of PT. Elang Mahkota Teknologi, Tbk. This is evidenced by the test results, which show a calculated F- value of 5.728 > F-table value of 4.256 with a significance level of 0.052 > 0.05. This can also be seen from the R-Square value of 0.639 or 63.9%, which means that the variables Current Ratio and Debt to Equity Ratio contribute 63.9%, while 36.1% is influenced by other variables not explained in this study.